Systematic evaluation of soil relative density effects on buried pipeline response to reverse-faulting: Evidence from physical model tests - Rohan Deb; Bithin Ghorai; Subhadeep Banerjee (Bulletin of Engineering Geology and the Environment, 2026)

Composite Heat Wave Risk (CHWR) framework using Principal Component Analysis (PCA) and machine learning for assessing agro community resilience - Dolgobinda Pal; Saon Banerjee; Nidhi Nagabhatla; Sarath Chandran M. A.; Amitava Panja; Sarathi Saha; Manish Kumar Naskar; Subhadeep Sarkar (Journal of Environmental Management, 2026)

Influence of rubber size and content on the cyclic and post-cyclic behaviour of Rubber-Sand Mixtures - Akshat Srivastava; Lucia Mele; Subhadeep Banerjee; Alessandro Flora (Soil Dynamics and Earthquake Engineering, 2026)

Predictive Estimation of Bending Strain and Active Length in Buried Pipelines Crossing Reverse Slip Faults - Rohan Deb; Bithin Ghorai; Subhadeep Banerjee (Geotechnical and Geological Engineering, 2026)

Upcycling edible Musa balbisiana bracts waste into sustainable and possible 3D printable biomaterials - Shivam Rajput; Dipjyoti Sharma; Koushik Nandan Dutta; Subhadeep Roy; Subham Banerjee (Innovative Food Science & Emerging Technologies, 2025)

Isolated Bilateral Cerebellar Dysfunction as the Initial Manifestation of HIV Infection: A Diagnostic Challenge, Case Report, and Literature Review - Ritwick Mondal; Shramana Deb; Ananya Sengupta; Subhadeep Banerjee; Nirmalya Ray; Mona Tiwari; Jayanta Roy; Julián Benito-León (The Cerebellum, 2025)
Despite widespread access to antiretroviral therapy, neurological complications remain common in people living with human immunodeficiency virus (HIV). While opportunistic infections and HIV-associated malignancies are the usual causes, there is growing recognition of atypical, non-opportunistic neurological syndromes as early manifestations of HIV infection—even in the absence of prior diagnosis or treatment. We report the case of a 46-year-old woman with type 2 diabetes mellitus and a history of pulmonary tuberculosis who presented with a two-month history of progressive unsteady gait, dysarthria, and frequent falls. Neurological examination revealed isolated cerebellar dysfunction. Brain magnetic resonance imaging showed T2 and FLAIR hyperintensities in the bilateral middle cerebellar peduncles and adjacent white matter, suggestive of rhombencephalitis. Extensive diagnostic work-up for infectious, autoimmune, and paraneoplastic etiologies was negative. HIV testing revealed dual seropositivity for HIV-1 and HIV-2, with undetectable HIV-1 RNA and a low CD4 + T-cell count. The patient improved clinically with supportive care and was referred for antiretroviral therapy. At the two-month follow-up, she demonstrated marked recovery. Although cerebellar involvement in HIV is typically associated with opportunistic infections or neoplasia, this case illustrates that bilateral cerebellar dysfunction can represent the first clinical manifestation of HIV infection. We also review previously reported cases in which cerebellar signs were the initial presentation, emphasizing the need to consider HIV testing in patients with unexplained cerebellar syndromes.

3D numerical analysis of liquefaction mitigation using ordinary and encased granular columns - Natarajan Dinesh; Subhadeep Banerjee; Karpurapu Rajagopal (Soil Dynamics and Earthquake Engineering, 2024)

An integrated approach to understand the regulatory role of miR-27 family in breast cancer metastasis - Sohini Chakraborty; Utpalendu Paul; Subhadeep Banerjee; Debanjan Saha; Satarupa Banerjee (BioSystems, 2024)

Physicochemical effects of pore fluid on the dynamic behavior of reconstituted marine clay - Swagatika Senapati; Subhadeep Banerjee; T. Thyagaraj (Marine Georesources & Geotechnology, 2023)

Shaking table experiments on framed structure resting on geogrid reinforced geotechnical seismic isolation system - J. S. Dhanya; Mohamed Aleem Fouzul; Subhadeep Banerjee; A. Boominathan; Askar Zhussupbekov (Bulletin of Earthquake Engineering, 2023)

Type II diabetes mellitus and obesity: Common links, existing therapeutics and future developments - Subhadeep Banerjee; Indrani Talukdar; Arnab Banerjee; Arnav Gupta; Advait Balaji; Raviprasad Aduri (Journal of Biosciences, 2019)

MicroRNAs play an important role in contributing to arsenic susceptibility in the chronically exposed individuals of West Bengal, India - Nilanjana Banerjee; Subhadeep Das; Sucheta Tripathy; Apurba K. Bandyopadhyay; Nilendu Sarma; Arun Bandyopadhyay; Ashok K. Giri (Environmental Science and Pollution Research, 2019)

Factors Affecting Strength and Stiffness of Dry Sand-Rubber Tire Shred Mixtures - B. R. Madhusudhan; A. Boominathan; Subhadeep Banerjee (Geotechnical and Geological Engineering, 2019)

Factors Affecting Post-cyclic Undrained Shear Strength of Marine Clay - Balaji Paramasivam; Subhadeep Banerjee (Geotechnical and Geological Engineering, 2017)

Parametric Study and Centrifuge-Test Verification for Amplification and Bending Moment of Clay–Pile System Subject to Earthquakes - Subhadeep Banerjee; Minu Joy; Debdeep Sarkar (Geotechnical and Geological Engineering, 2016)

Critical State Parameters of Dredged Chennai Marine Clay Treated with Low Cement Content - Palanidoss Subramaniam; Mohanachandra Menon Sreenadh; Subhadeep Banerjee (Marine Georesources & Geotechnology, 2016)